Effect of FeO content on melting characteristics and structure of nickel slag - Ma Y.-T.; Yang P.; Lu B.-G.; Dou Y.-L.; Tian J.-K.; Guo W.-B.; Zhang Z.-Q.; Shen Y.-Y. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Nickel smelting produces a large amount of nickel slag which contains a lot of Fe in the form of FeO. The effect of FeO content on the melting properties and structure of nickel slag is investigated by thermodynamic calculations and experiments, using the nickel slag of water quenching furnace as raw material, which is simplified to CaO-SiO2-FeO-MgO slag system. The results are as follows: with increasing FeO content, the precipitated primary phase changes from melilite to olivine. The liquidus temperature, softening temperature, hemispherical temperature, flow temperature, viscosity, and critical viscosity temperature of the slag system tend to decrease gradually, but the solid phase temperature tends to decrease first and then increase. The centre of the symmetric stretching vibration band of the [SiO4]4 tetrahedron -in the slag system shifts to the low wavenumber region. The mole fraction of O0 in the slag continuously decreases, and the mole fraction of O- and O2- increases. The complex silicon-oxygen tetrahedron structure gradually disintegrates and the structural unit tends to be simple.